Implementation of Sharia Marketing in The Digital Era to Improve Consumer Trust and Loyalty in Online Stores - Nur Sakinah; Fauzan Abdul Syakur; Indra Kurniawan (Education and Sociedad Journal, 2025)
This study aims to analyze the implementation of Islamic marketing in the digital era in enhancing consumer trust and loyalty at Zada Olshop in Sengkemang Village. This study employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. Data were analyzed using the Miles and Huberman model and validated through source triangulation. The findings reveal that Zada Olshop has implemented Islamic marketing principles through honesty, trustworthiness, transparency, good service, and the utilization of digital media in marketing activities. These practices have fostered consumer trust, which in turn has strengthened customer loyalty, as reflected in repeat purchases, customer satisfaction, and consumers’ willingness to recommend the products to others. Therefore, Islamic marketing in the digital era serves as an effective strategy for maintaining business sustainability in accordance with Islamic economic principles.